(untitled) (Eurasian Journal of Ecology, 2016)
In the article is resulted the short historical review of a condition and prospect of restoration of a rare unical species of a rubber-bearing plant Tau-sagyz. It’s presented introduction techniques in culture and the organizations of nurseries. Have been described the prospects of the use biotechnological methods (micro propagation) for obtain of new lines of tau-sagyz with the high content of rubber.